Slniečko 1995-1996: mesačník pre deti. Čís. 1-10 : Ročník 50 - Sliacky, Ondrej: 1941-; Čepčeková, Elena: 1922-1992; Ďuríčková, Mária: 1919-2004; Turan, Ján: 1932-; Hronský, Jozef Cíger: 1896-1960; kolektív autorov; Augustínová-Rochovanská, Božena: 1939-2005; Kellenberger, Martin: 1957-; Smetanová-Jendrejáková, Katarína: 1964-; Čapka, Marián: 1950-; kolektív ilustrátorov; Fabianová, Viera; et al. (Knižnica Slniečka, 1996)
Kniha obsahuje jednotlivé čísla časopisu Slniečko z rokov 1995-1996.